Main‐chain alternating fullerene and dye oligomers for organic photovoltaics. Issue 3 (20th October 2016) - Stephen, Meera; Dowland, Simon; Gregori, Alberto; Ramanitra, Hasina H; Santos Silva, Hugo; Combe, Craig MS; Bégué, Didier; Dagron‐Lartigau, Christine; Morse, Graham E; Genevičius, Kristijonas; Arlauskas, Kestutis; Juška, Gytis; et al.
Abstract: This work demonstrates for the first time that it is possible to prepare alternating oligomers, containing both dyes and fullerenes in repeating structures, that act as electron acceptors in bulk heterojunction devices. A sterically controlled azomethine ylide cycloaddition polymerization is employed with either C60 or phenyl‐C61 ‐butyric acid methyl ester (PCBM) and the dye diketopyrrolopyrrole (DPP). The former results in low molecular weights of around 5600 g mol −1, whereas the latter, PCBM, enables the formation of more soluble chains with higher molecular weights of ca 11 200 g mol −1 . Remarkably, cyclic voltammetry shows that the incorporation of PCBM into the main‐chain raises the lowest unoccupied molecular orbital by ca 380 meV due to the in‐chain bis‐additions. The observation of the complete quenching of DPP fluorescence by the fullerene moiety, combined with computer modelling studies, indicates both electron and energy transfers between intra‐chain moieties. Proof‐of‐concept devices show low efficiencies most likely due to as‐yet‐unoptimized preparation and structures, but hint at the possibilities of these novel bi‐functionalized, in‐chain fullerenes due to their high V oc of 0.89 V with an example low‐bandgap polymer, KP115, and reasonable charge mobilities of ca 1 × 10 −4 cm 2 V −1 s −1, making this new class of materials of strong interest for applications. Furthermore, their good thermal stability to above 300 °C and their stabilization of photovoltaic devices against thermal degradation confirm that this new pathway to a wide range of dye/fullerene structures is extremely promising. © 2016 Society of Chemical Industry Abstract : First examples of robust SACAP alternating fullerene and dye oligomers are demonstrated to show high LUMOs and Vocs in organic photovoltaic devices of 0.89 V.